1990
DOI: 10.1084/jem.172.2.599
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of tumor necrosis factor receptors by activated human neutrophils.

Abstract: SummaryThe capacity of human neutrophils (PMN) to bind tumor necrosis factor (TNF) was rapidly lost when the cells were incubated in suspension with agents that can stimulate their migratory and secretory responses . Both physiological (poly)peptides (FMLP, C5a, CSF-GM) and pharmacologic agonists (PMN, calcium ionophore A23187) induced the loss ofTNF receptors (TNF-R) from the cell surface. Half-maximal loss in TNF-R ensued after only ti2 min with 10 -7 M FMLP at 37°C, and required only 10-9 M FMLP during a 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
181
2
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(192 citation statements)
references
References 56 publications
6
181
2
1
Order By: Relevance
“…The soluble forms originating from the extramembranous portion of the TNF-RI (sTNF-RI) and TNF-RII (sTNF-RII) can be found in the culture supernatants of lymphocytes, monocytes and neutrophils [15,[19][20][21] and biological fluids [22,23]. The elevation of sTNF-R in serum/plasma and biological fluids reflecting a variety of inflammatory disorders has been shown in several diseases [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The soluble forms originating from the extramembranous portion of the TNF-RI (sTNF-RI) and TNF-RII (sTNF-RII) can be found in the culture supernatants of lymphocytes, monocytes and neutrophils [15,[19][20][21] and biological fluids [22,23]. The elevation of sTNF-R in serum/plasma and biological fluids reflecting a variety of inflammatory disorders has been shown in several diseases [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the surface expression of both receptors decreases considerably when PMN are exposed to TNF and various agents including FMLP, the tumor promoter PMA, the Ca 2ϩ ionofore A23187, endotoxin, and GM-CSF (11)(12)(13). The decrease in receptor expression occurs via a process known as shedding, whereby the extracellular portion of the receptors is proteolytically cleaved and released in a soluble form that maintains the ability to bind TNF (11,14). With TNF, receptor down-modulation has been shown to occur via internalization of TNF-R55 and shedding of TNF-R75 (14).…”
mentioning
confidence: 99%
“…Because PMN rapidly and extensively release their TNF receptors after adherence or exposure to various agonists (11)(12)(13), it has been suggested that these cells might be a significant source of increased circulating TNF receptors observed in physiologic and pathologic conditions such as exercise (19), experimental endotoxemia (20), a clinical model of postoperative sepsis (21), and high-dose TNF in isolated limb perfusion (22). In light of these observations, the comprehension of the mechanisms that regulate shedding in PMN might provide the basis for experimental approaches aimed at modulating systemic responses to TNF.…”
mentioning
confidence: 99%
“…18 Similar to TNF, elevated levels of soluble TNFR2 (sTNFR2) in serum or other body fluids has been recognized as a predictor of pathological conditions, such as sepsis, infections, hepatitis, organ fibrosis, cancer development and other inflammatory diseases. 19,20 In vitro experiments demonstrated that sTNFR2 can be rapidly shed from activated BM-derived cells, such as neutrophils and cultured mononuclear cells, upon TNF, lipopolysaccharide (LPS) or IL-10 stimulation.…”
Section: Introductionmentioning
confidence: 99%